2011
DOI: 10.1364/ao.50.001850
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of extremely weak optical scattering from an interlocking carbon nanotube array

Abstract: We experimentally demonstrate a nearly wavelength-independent optical reflection from an extremely rough carbon nanotube sample. The sample is made of a vertically aligned nanotube array, is a super dark material, and exhibits a near-perfect blackbody emission at T=450 K-600 K. No other material exhibits such optical properties, i.e., ultralow reflectance accompanied by a lack of wavelength scaling behavior. This observation is a result of the lowest ever measured reflectance (R=0.0003) of the sample over a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…New magnetic nanocomposites based on carbon nanotubes (CNTs) [ 1,2,3] are very promising for high frequency applications [ 4,5,6,7,8,9,10,11,12,13,14] such as transmission lines, mixtures and detectors [15,16,17], antennas and absorbing materials [18,19,20,21,22,23,24,25,26]. The absorption properties of CNT-based nanocomposites are primarily determined by the dielectric loss [27].…”
Section: Introductionmentioning
confidence: 99%
“…New magnetic nanocomposites based on carbon nanotubes (CNTs) [ 1,2,3] are very promising for high frequency applications [ 4,5,6,7,8,9,10,11,12,13,14] such as transmission lines, mixtures and detectors [15,16,17], antennas and absorbing materials [18,19,20,21,22,23,24,25,26]. The absorption properties of CNT-based nanocomposites are primarily determined by the dielectric loss [27].…”
Section: Introductionmentioning
confidence: 99%
“…These polarization dependent absorption, transmission, reflection, and resonant scattering properties have been studied by spectroscopic techniques ranging from terahertz (THz) and far-infrared4567891011, to infrared and visible1213141516 spectroscopy as well as the Raman1718 and pump-probe spectroscopic techniques4567. The results of these measurements have convincingly demonstrated that the anisotropic absorption and scattering will reach the maximum and the minimum in the opposite extreme conditions when the light is parallel and perpendicular to the nanotube axis, respectively.…”
mentioning
confidence: 98%
“…[4][5][6][7] A large number of studies have focused on the optical characterization of these materials from the ultraviolet to the microwave regions. 1,[4][5][6][7][8][9][10][11][12][13][14][15] Vertically aligned carbon nanotube (VACNT) films appear black with an extremely low reflectance from the visible to the far-infrared; hence, they are ideal for radiation detection, energy harvesting, and space-borne infrared systems. [4][5][6][7][8][9] Most studies on VACNT films dealt with the reflectance, and little has been done to determine the absorption coefficient of VACNT films in the near-and mid-infrared region.…”
mentioning
confidence: 99%
“…The low reflectance is due to the close-to-unity n of the VACNT film. [6][7][8][9] A laser scatterometer was used to measure the specular reflectance at 4 incidence angle at k ¼ 635 nm. The ratio of the specular reflectance to R dh gives the specularity, which can be related to an apparent root-mean-square roughness of (150 6 20) nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation